Potency of Bancassurance-A General Overview - Diksha Sadana; Dr. Kamalpreet Kaur (HM Journals, 2024)
From a constrained, closed economy in the 1950s to an open, liberalized economy as it is today, India's economy has come a long way. It took over 40 years to bring about the required reforms for the bilateral growth of the Indian economy relative to the global economy; hence the transformation did not occur in a single day. The nationalization of banks provided the sector with much-needed capital where the flow of funds was constrained, and the sector had a substantial impact on the development of the economy. Private players' arrival has significantly altered the way business is conducted, and they have chosen to create a new distribution model called